Some approximation properties of Urysohn type nonlinear operators - KARSLI, Harun (Studia Universitatis Babeș-Bolyai Mathematica, 2019)
The central issue of this paper is to continue the investigation of convergence properties of Urysohn type operators. By using Urysohn type operators we will extend the theory of interpolation to functionals and operators. In details, the present paper centers around Urysohn type nonlinear counterpart of the two dimensional Stancu operators defined on a triangle. We construct our nonlinear operators by defining a nonlinear forms of the kernel functions. Afterwards, we investigate the convergence problem for these operators. Mathematics Subject Classification (2010): 41A25, 41A35, 47G10, 47H30.